(untitled) (HEALTH CARE: JURNAL KESEHATAN, 2024)
Pulmonary tuberculosis (TB) is an infectious disease that is still a public health problem, especially in developing countries, including Indonesia. The problems faced influence disease, discovery, treatment, and also treatment failure. The aim of this research is to determine the determinant factors related to the incidence of pulmonary TB in the working area of ​​the Kenten Laut Community Health Center, Banyuasin Regency in 2024. The research design is a quantitative analytical survey with a cross sectional approach. The population in this study were all patients with cough complaints that lasted ≥ 2 weeks who received treatment at the Kenten Laut Community Health Center, a total of 901 patients. Sampling using Slovin theory. The sample in this study amounted to 98 respondents. The sampling method uses purposive sampling. This research was carried out from March 1, 2024 to April 2, 2024. Data was collected using a questionnaire. Bivariate data analysis used Chi-Square and multivariate tests. Keywords : Determinants, Incidence, Pulmonary TB